Promoting oral and dental health in early childhood - knowledge, views and current practices among paediatricians in Israel - Shmueli, Aviv; Assad-Halloun, Aida; Fux-Noy, Avia; Halperson, Elinor; Shmueli, Einat; Ram, Diana; Moskovitz, Moti (Frontiers in Pediatrics, 2023)
Early childhood caries is the most prevalent disease in childhood. Paediatricians are considered by parents as the main authority on prevention and treatment of all the health requirements of their infants. Aim: The aim of this study was to evaluate the knowledge and practice of paediatricians in promoting oral and dental health among young patients (until age 36 months) and their parents. Materials and methods: The survey was conducted with a self-filled questionnaire that was distributed among paediatricians at the national convention of the Israeli Association of Clinical Paediatrics, in paediatric ambulatory clinics and paediatric departments in hospitals. Demographic variables, awareness to the guidelines of the American Association of Pediatrics on early childhood caries, medical training and post-graduate education were recorded. Results: The results of the survey showed that most paediatricians recognize their role in maintaining oral and dental health of their young patients. Nevertheless, most admitted that they do not perform simple procedures like dental examinations, or asking parents about feeding habits or teeth brushing. Only 21% of the participants expressed adequate knowledge of dental care for children younger than age 3 years. Fifty-eight percent of the participants never had any dental training during their entire paediatric medicine training, including medical school. Conclusion: Oral and dental knowledge should be incorporated into the paediatric medicine curriculum. With their heavy workload, paediatricians generally do not implement caries risk assessment and counselling.